DRIVE-THRU REVOLUTION: ENHANCING CUSTOMER SATISFACTION THROUGH DIGITAL TWINS - Lanawaang, Yehuda Marcel; Suryawijaya, Tito Wira Eka (Business Management Analysis Journal (BMAJ), 2024)
In business, understanding consumers is paramount. Digital Twins technology provides virtual representations of consumers and real-time insights. This study evaluates the implementation of Digital Twins in drive-thru services, focusing on efficiency and user experience. A survey was conducted with 2000 drive-thru consumers in the US and analyzed using SEM-PLS. The findings of this study indicate the significance of Digital Twins in purchase accuracy, interactivity, and satisfaction. The importance of strategic implementation is highlighted to maximize benefits and offer a framework for secure implementation. Limitations of this research include geographical constraints of the respondents, data collection methods, and limitations in relevant literature due to the new nature of Digital Twins technology in the context of drive-thru services. Future research needs to explore cross-cultural comparative research, longitudinal studies, and mixed-methods approaches to further understand the impact of this technology.